Quadro metodológico para avaliação quantitativa de projetos de urbanização, sob a ótica da interação água e cidade - Battemarco, Bruna Peres (2020)
This work proposes a methodological framework that allows the evaluation of urbanization projects on a watershed, considering vulnerability reduction and increased resilience, thus reducing risks, as well as river and environmental restoration in the city and the efficiency of urban infrastructure. In order to map the watershed flood behavior in each scenario, as the first methodological step, a hydrodynamic mathematical modeling tool was used to support this task. Then the different dimensions considered in the project assessment were represented by multicriteria indexes, as follows: Flood Resilience Index (FResI), Flood Vulnerability Index (FVI), Urban River Restoration Index (URRIx), Environmental Quality Assessment Index (EQAI) and Urban Infrastructure Efficiency Index (UIEI). These indexes together approach social, economic, infrastructure, and environmental aspects. FVI, EQAI and UIEI are original contributions, while FResI and URRIx are pre-existing indexes. Finally, the Design Evaluation Index (DEI) is proposed, which groups the individual results obtained for each index, providing a general integrated measure that aims to support decision making in choosing the best and most suitable design alternative for the place of interest. An application demonstration of the proposed methodology is carried out considering a case study Vargem Grande, a developing neighborhood in the West Zone of the city of Rio de Janeiro.